Article Penerapan Model Jigsaw dalam Pembelajaran Membaca Pemahaman berbantuan Buku Digital - Yuzzara Zahwa Priatna; Prana Dwija Iswara; Dadan Djuanda (Universitas Cokroaminoto Palopo, 2024)
Preliminary studies show that reading skills have not become a habit for fourth grade students. This fact becomes the background of the problem in students' reading comprehension learning. Students have difficulty answering questions about events experienced by characters and are still confused in capturing information in a text. Students are still confused in determining their opinion about the message of the story. One of the efforts to improve reading comprehension skills is to use the Jigsaw learning model with the help of digital books. This study used a classroom action research method with a qualitative design with data collection techniques in the form of tests, observations, and field notes. The subjects of this study were 24 fourth grade students of SDN in North Sumedang District, Sumedang Regency. The criteria for achieving learning objectives (KKTP) in this subject is 70 with a learning completeness target of ≥85%. Based on the results of the actions provided, the percentage of student learning outcomes in the pre-action reached 8.33%, in cycle I increased to 45.83%, in cycle II increased to 87.50% which means that learning in cycle II has reached the target of learning completeness.